Trading up and down: Toward a hybrid purchase style - masmoudi, manel (Journal of Contemporary Research in Management (JCRM), 2017)
This research aims to study a new trend in consumer behavior that could be concretized in adopting both of the "trading up" and "trading down" behaviors. A qualitative study using semi-structured ethnographic interviews highlights a new purchase style, which we called them the "hybrid purchase style". This exploratory work provides a first insight about the theoretical and the conceptual framework that could in turn provide perspectives for understanding and eventually modeling this new purchasing style. It describes a set of motivations, opinions, and behaviors favoring the purchase of high and low range products. Three main orientations were detected through this investigation: social, emotional and rational facets.